Designing Transactional Conversation Videos as Supplementary Materials to Support Teaching English Speaking Skill: (A Design and Development Research to the Second Semester Students of EESP of Universitas Tanjungpura in Academic year 2021/2022) - Siswanto, Febry; Rahayu Apriliaswati; Wardah (Kirana Publisher (KNPub), 2023)
This research was aimed at designing transactional conversation videos as supplementary materials to support teaching English speaking skills. This research is a design and development research adopted from the ADDIE model. The respondents of this research were the second semester students of English Education Study Program (EESP) Universitas Tanjungpura. This research was done by three phases of the ADDIE approach, which is ADD. In the Analyze phase, the researcher observed the students’ and the teacher’s needs and the syllabus applied. In the Design phase, the researcher observed examples of good product videos, theories, and references for making the video. In the Develop phase, the researcher used Adobe Premier Pro to develop learning videos for the students. It was found that the design of the product was successfully integrated with the syllabus and met the criteria of success in product validation. The result of validation showed that the applied video with the Student’s book was helpful for the students to support them in learning to speak for Transactional Functions.